2014
DOI: 10.1007/s00404-014-3501-4
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Tumor markers in mature cystic teratomas of the ovary

Abstract: Unfortunately, the given and family names of the complete author group was interchanged in the official publication of the article. The correct author group is given below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Ustunyurt et al (6) reported that serum CA19-9 is the most reliable tumor marker of mature ovarian cystic teratomas, and that the levels of serum CA19-9 are often associated with the size of the teratoma; however, this does not appear to have high specificity or sensitivity. Bast et al (7) reported that serum CA-125 is a reliable marker, and that in combination with elevated CA19-9, it may be a differential character of malignant tumors.…”
Section: A B C Dmentioning
confidence: 99%
“…Ustunyurt et al (6) reported that serum CA19-9 is the most reliable tumor marker of mature ovarian cystic teratomas, and that the levels of serum CA19-9 are often associated with the size of the teratoma; however, this does not appear to have high specificity or sensitivity. Bast et al (7) reported that serum CA-125 is a reliable marker, and that in combination with elevated CA19-9, it may be a differential character of malignant tumors.…”
Section: A B C Dmentioning
confidence: 99%
“…A study of 215 pathologically confirmed MCT's found the preoperative mean serum CA 19-9 level to be 83.5 ± 179.2 U/ mL with an overall elevated rate of 39.6% [6]. Comparatively, CA 125 was elevated above its threshold value in 23.3% of the patient population, and AFP was elevated above threshold in only 0.6% of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Mature cystic teratomas compromise 10-20% of all ovarian neoplasms and they commonly present in woman aged 20 to 40 years old [6]. We present this case in order to build on the growing body of evidence suggesting that CA 19-9 levels are useful in the diagnosis and management of MCT [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Because of these features benign cystic teratoma can present with elevation of tumour markers of CA 19-9 and CA 125. 15 The most common malignant transformation of is invasive Squamous cell carcinoma, others being Adenocarcinoma, Sarcoma, Carcinoid, Thyroid carcinoma and Melanoma. 16,17 The correlation between high serum tumour markers and tumour size is due to leakage of cyst contents into bloodstream because of rupture or weakened cyst wall due to larger tumour diameter.…”
Section: Discussionmentioning
confidence: 99%